Molecular memories in the regulation of seasonal flowering: from competence to cessation. Issue 1 (December 2015) - Bratzel, Fabian; Turck, Franziska
Abstract Plants commit to flowering based on endogenous and exogenous information that they can remember across mitotic cell divisions. Here, we review how signal perception and epigenetic memory converge at key integrator genes, and we show how variation in their regulatory circuits supports the diversity of plant lifestyles.